2006
DOI: 10.1111/j.1525-1438.2006.00300.x
|View full text |Cite
|
Sign up to set email alerts
|

CAG repeat length in exon 1 of the androgen receptor gene is related to age of diagnosis but not germ line BRCA1 mutation status in ovarian cancer

Abstract: It has been postulated that androgens, through their interaction with androgen receptors (AR), may play an important role in the development of ovarian cancer. Exon 1 of the AR gene contains three highly polymorphic trinucleotide repeats. The length of the (CAG)n repeat segment 1 is inversely correlated with the transactivation function of the AR. Recent studies have shown that BRCA1 may function as an AR coregulator or coactivator and play positive roles in androgen-induced cell death in cancer cells as well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…It has been postulated that androgens, through their interaction with androgen receptors, may play an important role in the development of specific tumors, such as ovarian and prostate cancer [16,17]. Exon 1 of the AR gene contains highly polymorphic trinucleotide repeats, and the length of the nCAG repeat segment is inversely correlated with the transactivation function of the AR gene [18].…”
Section: Discussionmentioning
confidence: 99%
“…It has been postulated that androgens, through their interaction with androgen receptors, may play an important role in the development of specific tumors, such as ovarian and prostate cancer [16,17]. Exon 1 of the AR gene contains highly polymorphic trinucleotide repeats, and the length of the nCAG repeat segment is inversely correlated with the transactivation function of the AR gene [18].…”
Section: Discussionmentioning
confidence: 99%
“…In two studies comprising patients with both hereditary and sporadic ovarian cancers, those with shorter CAG repeats were shown to be diagnosed an average of 7.2 (CAG <15; 95% CI = 2.3–12.1, P = 0.004) [34] or 10.45 (CAG ≤22; 95% CI = 1.28–19.62, P = 0.02) [35] years earlier than those with longer repeats. Correspondingly, as seen in prostate cancer [36], case-control studies involving ovarian cancer patients and unaffected control subjects have indicated that short CAG repeats are associated with a significantly higher risk of developing ovarian tumor in African Americans in the US [37], Polish Caucasians [38], or Han Chinese [39,40].…”
Section: Role Of Androgens and Ar Signaling In Ovarian Carcinogenesismentioning
confidence: 99%
“…There are several published studies that addressed the association between AR repeat polymorphisms and ovarian cancer [ 6 , 12 , 14 17 ]. However, none was conducted in non-Asians.…”
Section: Introductionmentioning
confidence: 99%